1971
DOI: 10.1159/000178232
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Histoenzymological Properties of the Supraoptic and Paraventricular Nuclei and of Other Nuclear Regions of the Hypothalamus, the Epithalamus-Epiphysis Region and the Subfornical Organ

Abstract: In the hypothalamus of white rats ganglion cell groups can be observed which show enzyme histochemical properties (low SDH and CYO, moderate G6PDH and TPND and marked LDH and MDH activity) similar to those of the supraoptic and paraventricular nuclei performing secretory function. These cell groups are the accessory magnocellular cell groups, those radiating from the paraventricular nucleus, all the cells of the nucleus tuberomamillaris as well as cells located in the area of the nucleus periventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…As regards the functional morphological connexions, reference is made to the review of Leonhardt [14], In our experience, the oxidative enzyme structure of the tanycyte ependyma, the subfornical and subcommissural organs, which presumably exert secretory activity, and the various hypothalamic peptider gic neurones are similar in many respects (low SDH andCYO, and significant LDH. GbPD and TPND activities) [2], There is an essential difference, however, that the tanycyte ependyma does not possess TPPase activitylocalised [18,22] on the cisterns of the Golgi apparatus and important in protein synthesis nor acid phosphatase activity [24], which are character istic for the others. According to the autoradiographic observations of F ujita [8], the ependymal cells of an adult mouse do not exhibit a tendency to protein secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As regards the functional morphological connexions, reference is made to the review of Leonhardt [14], In our experience, the oxidative enzyme structure of the tanycyte ependyma, the subfornical and subcommissural organs, which presumably exert secretory activity, and the various hypothalamic peptider gic neurones are similar in many respects (low SDH andCYO, and significant LDH. GbPD and TPND activities) [2], There is an essential difference, however, that the tanycyte ependyma does not possess TPPase activitylocalised [18,22] on the cisterns of the Golgi apparatus and important in protein synthesis nor acid phosphatase activity [24], which are character istic for the others. According to the autoradiographic observations of F ujita [8], the ependymal cells of an adult mouse do not exhibit a tendency to protein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…We reported in our earlier papers [1,2] on the more significant GfiPD, TPDN, and TPPase activities of the top of the inframammillary recess compared to the ciliated ependyma elsewhere lining the third ventricle. Colmant [4] has demonstrated that the activity of TPND is locally stronger on the dorsal part of the third ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation